1994
DOI: 10.1017/s0003356100007467
|View full text |Cite
|
Sign up to set email alerts
|

Crossbreeding Jersey with Ghana Shorthorn and Sokoto Gudali cattle in a tropical environment: additive and heterotic effects for milk production, reproduction and calf growth traits

Abstract: Crossbreeding data involving Ghana Shorthorn, Sokoto Gudali and their Jersey F1s and backcrosses collected over a 16-year period were analysed to estimate additive and heterotic effects for milk production, reproduction and calf growth traits. Sokoto Gudali was significantly better than Ghana Shorthorn in all milk production traits. Calving interval and annualized milk production were better in Gudali than in the Shorthorn. The F1s had higher lactation milk yield, milked longer, produced their first calves ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
27
4
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 9 publications
22
27
4
4
Order By: Relevance
“…For example, 50% Holstein crosses had a fourfold increase over the Ethiopian Boran breed in terms of LYD, 305YD, DM and LTYD; they were also milked for 97 more days than Ethiopian Boran. Except for the magnitude of differences, the superior performance of crossbred progeny compared with the Ethiopian Boran for milk production traits is as expected and is in agreement with comparative results reported for Bos indicus and their crosses with European dairy breeds in the tropics (IAR, 1982;Kiwuwa et al, 1983;Thorpe et al, 1993;Rege et al, 1994;Udo et al, 1995;Demeke et al, 2004). When the crosses were compared, it was observed that as the exotic inheritance level increased, LYD, 305YD and DM showed an increasing trend.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…For example, 50% Holstein crosses had a fourfold increase over the Ethiopian Boran breed in terms of LYD, 305YD, DM and LTYD; they were also milked for 97 more days than Ethiopian Boran. Except for the magnitude of differences, the superior performance of crossbred progeny compared with the Ethiopian Boran for milk production traits is as expected and is in agreement with comparative results reported for Bos indicus and their crosses with European dairy breeds in the tropics (IAR, 1982;Kiwuwa et al, 1983;Thorpe et al, 1993;Rege et al, 1994;Udo et al, 1995;Demeke et al, 2004). When the crosses were compared, it was observed that as the exotic inheritance level increased, LYD, 305YD and DM showed an increasing trend.…”
Section: Discussionsupporting
confidence: 88%
“…Demeke et al (2004), on the other hand, reported a comparable additive breed effect in the crosses of Holstein and Ethiopian Boran in Ethiopia. The estimates for individual heterosis effects are within the range of reported heterotic effects for milk production traits of other B. taurus 3 B. indicus crosses (Sharma and Pirchner 1991;Thorpe et al, 1993;Rege et al, 1994;Mackinnon et al, 1996;Rege, 1998, Demeke et al, 2004.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Esses resultados confirmam aqueles encontrados por Lemos et al (1992), em que as F1 tiveram primeiro parto mais jovens e as 5/8 em idade mais avançada. Rege et al (1994), estudando o desempenho de animais mestiços Jersey x Ghana Shorthorn (Bos taurus) e Jersey x Sokoto Gudali (Bos indicus), observaram que animais F 1 apresentaram menores idades ao primeiro parto que os puros (Ghana Shorthorn ou Sokoto Gudali), porém, ao contrário do observado neste estudo, os animais F1 apresentaram IPPs semelhantes às dos animais produzidos por retrocruzamento (3/4 de genes da Raça Jersey).…”
Section: Resultsunclassified
“…The variation in milk production performance over periods may not only be caused by inter-annual random change of the climatic factors, but may also include management changes over periods. Inter-annual variation in milk production for grazing dairy cows is a common phenomenon in tropical dairy production systems (Kiwuwa, et al, 1983;Thorpe et al, 1993;Rege et al, 1994;Demeke et al, 2004;Haile et al, 2009). …”
Section: Genetic and Non-genetic Effectsmentioning
confidence: 99%